Effect of Terminal High Temperature Imposed by Late Sowing on Phenological Traits of Wheat (Bangladesh Agronomy Journal, 2015)
Phenological performance in relation to yield of wheat genotypes; BARI Gom 26, BAW 1051, BARI Gom 27 and BARI Gom 28 were evaluated under normal and heat stress environments. One irrigated timely sowing (ITS) and three irrigated late sowings (ILS) were imposed to provide terminal high temperature over the tested genotypes. The ITS was November 25 and three ILS were December 10, December 25 and January 10. In heat stress condition, the genotypes phased a significant level of high temperature stress which affected on phenological stage and yield compared to ITS. In ITS situation, days to anthesis and booting decreased in heat stress condition regardless the cultivars. The phenological characteristics under heat stressed condition led the wheat cultivars to significantly lower grain yield as compared to normal condition. In heat stress situations (Dec 10Jan 10), the average grain yield was reduced by12.8 -39.8 % in BARI Gom 26, 14.4-29.7% in BAW 1051, 11.5-26.5% in BARI Gom 27 and 17.4-25.6 % in BARI Gom 28 in both the season. It was also observed that grain yield was found to be reduced by about 7.7-15.4% in BARI Gom 26, 9.4-15.7 % in BAW 1051, 9.4-12.4% in BARI Gom 27 and 9.7-12.0% in BARI Gom 28 from ITS for each 1°C rise in average mean air temperature during booting to maturity. On the other hand, reduction percent were less for the new varieties. Grain yield reduction was about 1.4 - 2.65% in BARI Gom 28, 0.1-6.7 % in BARI Gom 27 and 1.7-6.0% in BAW 1051.Bangladesh Agron. J. 2015, 18(1): 13-25